2004
DOI: 10.1097/00005344-200403000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-Steroidal Anti-Inflammatory Drugs on Amyloid-β Formation and Macrophage Activation after Platelet Phagocytosis

Abstract: Recently, we showed that platelet phagocytosis occurs in human atherosclerotic plaques and leads to foam cell formation. Platelet phagocytosis, resulting in macrophage activation and iNOS induction, was associated with the formation of amyloid-beta peptide (Abeta) via proteolytic cleavage of platelet-derived amyloid precursor protein (APP), possibly by secretases. To test the involvement of gamma-secretase in this process, we used indomethacin, ibuprofen, and sulindac sulfide, non-steroidal anti-inflammatory d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Only recently, Jans et al. showed that platelet phagocytosis by macrophages occurs in atherosclerotic plaques and results in foam cell formation involving amyloid β‐peptide [80]. Intriguingly, in our investigations we were able to show that dendritic cells also substantially internalize platelets, when coincubated over several days [81] (Fig.…”
Section: Dendritic Cells Platelets and Atherosclerosissupporting
confidence: 62%
“…Only recently, Jans et al. showed that platelet phagocytosis by macrophages occurs in atherosclerotic plaques and results in foam cell formation involving amyloid β‐peptide [80]. Intriguingly, in our investigations we were able to show that dendritic cells also substantially internalize platelets, when coincubated over several days [81] (Fig.…”
Section: Dendritic Cells Platelets and Atherosclerosissupporting
confidence: 62%
“…Immunohistochemical analysis of human atherosclerotic lesions identified b-amyloid peptides in activated perivascular macrophages that had phagocytosed platelets, supporting the notion that this mechanism promotes b-amyloid accumulation in vivo. Furthermore, a subset of nonsteroidal anti-inflammatory drugs that affect APP processing by g-secretase and b-amyloid generation in Alzheimer's disease also reduces macrophage activation after platelet phagocytosis and inhibits the formation of b-amyloid peptide [27]. Together, these data support a role for platelet-macrophage interactions in the generation of b-amyloid peptide in atheroma.…”
Section: B-amyloidmentioning
confidence: 69%
“…To strengthen this view and to clarify whether the observed effects were inherent to aspirin and sodium salicylate, cells were incubated with two well-known COX1/2 inhibitors, ibuprofen and naproxen. Corresponding to previous reports, we used increasing concentrations of ibuprofen and naproxen up to 100 mol/l and 300 mol/l, respectively (21)(22)(23). Neither compound was shown to influence SR-BI expression (Fig.…”
Section: Influence Of Different Nsaids On Sr-bi Regulationmentioning
confidence: 93%